El Excentrico, 1964-04-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
April 5, 1964 [5 de abril de 1964]. Ano 14, No 12. Cover has a photograph of five fashion models. PIctured from bottom to top are Patty Valenti, Armida Medina, Stella Maldonado, Lillian Lozano, and Magdalena Azdar.